Development Of An Animal Model To Recover Poly(3-Hydroxybutyrate) Granules From Dried Cells Of Cupriavidus Necator H16 - Balakrishnan, Kunasundari (2013)
The importance of developing an environmentally friendly and efficient recovery process of polyhydroxyalkanoates (PHAs) from bacterial cells motivated this research. One of the objectives of this study was to evaluate the welfare and tolerability of the animal model, Sprague Dawley given lyophilized cells of Cupriavidus necator H16 as sole diet source. C. necator H16 was cultured using a mineral medium containing crude palm kernel oil (CPKO) as the sole carbon source. The bacterial cells containing about 37 wt% of poly(3-hydroxybutyrate), P(3HB) were used as a source of protein. By taking into account the well-documented nutritive aspects of C. necator cells, the lyophilized cells were given as feed source to animal model (Sprague Dawley). Groups of 6 animals each for both sexes were fed with lyophilized cells of C. necator H16 for study intervals of 7, 14 and 28 days. No mortality was observed and the test animals were found to tolerate well with the whole cell diet. In comparison with the control animals, the test group showed poor weight gain. This is due to the fact that the actual nutritious portion of the feed received by test animals was less than half by weight as compared with the feed consumed by control animals. Haematology and serum biochemistry analyses did not reveal any significant abnormalities.